Analisis Potensi Biomassa Pertanian, Sampah Kota Dan Limbah Peternakan Dalam Perencanaan Kapasitas Pembangkit Listrik Di Provinsi Sulawesi Selatan - Andi Muhammad Akmal Abdussamad (Jur. Teknik Elektro Fak. Teknik UMY, 2016)

(untitled)
The source of electrical energy in Indonesia is still dominated by fossil fuel sources such as oil, natural gas, and coal are limited in number and are not renewable. Power plant by fossil fuel working by burning fossil fuels such as coal, natural gas, or petroleum to produce electrical energy. Indonesia as one of the developing countries need to seek new alternative for replacing fossil energy are depleting in numbers. The utilization of renewable sources of energy from agricultural biomass, biogas and municipal solid waste is one of the solution because, being able to reduce carbon dioxide emmisions and can minimize organic waste. Especially in South Sulawesi province, the potential power that can be generated by the source of energy of Biomass, Biogas and Municipal Solid Waste is in row of 1.096,34 MW, 118,92 MW and 1.033,06 MW.